Linux : network administrator's guide - Kirch, Olaf (O'Reilly, 1993)
"The Linux Network Administrator's Guide gives you all the information you need to join a network, whether you want a simple UUCP connection or a full LAN, with your Linux system serving as a firewall, an NFS or NIS file server, and a mail and news hub." "This book touches on all the essential networking software included with the operating system, plus some hardware considerations. Fully updated, the book now covers firewalls, including the use of ipchains and iptables (netfilter), masquerading, and accounting. Other new topics include Novell (NCP/IPX) support and INN (news administration). The original material on serial connections, UUCP, routing and DNS, mail and News, SLIP and PPP, NFS, and NIS has been thoroughly updated. Kernel options reflect the 2.2 kernel." "Topics include: introduction to TCP/IP; configuring network and serial hardware; Domain Name Service; serial line communications using SLIP and PPP; NIS and NFS; taylor UUCP; administering electronic mail, including sendmail and exim; Administering Netnews, including INN and several newsreaders; firewalling using ipfwadm, ipchains, and netfilter; masquerading and accounting; and IPX configuration for a Novell Netware network."--Jacket.